Obowiązki organizatorów w świetle standardów ochrony małoletnich – narzędzie zapobiegania przestępczości i zwiększenia bezpieczeństwa małoletnich - Kosowski, Jakub (PRAWO i WIĘŹ, 2025)
The paper deals with the obligations introduced by the so-called Kamilek Act and relating to the organisers of activities for minors. This issue is of key importance, considering that the obligations concern a wide group of entities, including public and private ones, conducting activities in key areas of social life, from education to extracurricular activities to hotel services. The paper describes in detail the obligations of the organisers of these activities. At the same time, it highlights significant doubts in the practical application of the law, which represent a major challenge for the organisers of activities. Within the framework of the de lege ferenda postulates, a number of solutions have been proposed, which are aimed at improving the fulfilment of obligations by the obligated entities, but also at increasing the quality of the fulfilment of obligations, for example in the context of the implementation of specialised training for staff.